A Self-Adaptive Clustering Algorithm for Wireless Sensor Network - Huan Yan; Zun-wen He; Jian-guang Jia (2009 5th International Conference on Wireless Communications, Networking and Mobile Computing, 2009)
The network routing could be simplified by clustering algorithm in wireless sensor network (WSN). Aimed at the occasion with a large amount of nodes but without whole-network time synchronization mechanism, a self-adaptive clustering algorithm for network topology control is proposed. In this algorithm, the cluster structure can be adjusted automatically according to the nodes distribution and network traffic. By adopting loop-avoidance mechanism, the correctness of routing selection is ensured when adjusting the cluster structure. The simulation results demonstrate that the proposed algorithm can reach the expected effect of self-adjustment.